Methylation of PCDH17 and NEFH as prognostic biomarker for nonmetastatic RCC: A cohort study. Issue 28 (15th July 2022) - Koudonas, Antonios; Papaioannou, Maria; Kampantais, Spyridon; Anastasiadis, Anastasios; Hatzimouratidis, Konstantinos; Dimitriadis, Georgios
Abstract : DNA methylation makes up a main part of the molecular mechanism of cancer evolution and has shown promising results in the prognosis of renal cell cancer (RCC). In this study, we investigated the possible association of promoter methylation of PCDH17, NEFH, RASSF1A, and FHIT, genes with the prognosis of nonmetastatic RCC patients. Cancerous and normal adjacent tissues from surgical specimens of 41 patients with long follow-up were treated for DNA isolation and bisulfite conversion. The gene promoter methylation was determined with quantitative methylation-specific PCR (qMSP). Wilcoxon signed-rank test was used for paired methylation comparisons, while univariate linear regression and Mann-Whitney test were applied for associating methylation status with clinical and disease characteristics. Cox regression proportional hazards models and Kaplan-Meier plots were used for survival analyses in reference to methylation status. Paired comparisons showed tissue-specific hypermethylation for PCDH17 ( P < .001), NEFH ( P < .001), RASSF1A ( P = .032), while a positive association of methylation in normal tissues with age was demonstrated for PCDH17 ( P < .001), RASSF1A ( P < .001), FHIT ( P < .001). PCDH17 was more methylated in cases with clear cell RCC ( P = .015) and high-grade tumor ( P = .013), while NEFH methylation was higher in locally advanced cases ( P = .032). PCDH17 hypermethylation in cancerous and normal tissues was linked to shorter disease-specific survival (DSS, P = .026, P = .004), disease-free survival (DFS, P = .004, P = .019) while NEFH hypermethylation in cancerous tissues was related to shorter DSS ( P = .032). Increased methylation difference of NEFH was also associated with shorter DSS ( P = .041) and DFS ( P = .020), while the corresponding parameter for PCDH17 was associated with poor DFS ( P = .014). Kaplan-Meier curves for hypermethylation in cancer tissues demonstrated different clinical courses for PCDH17 ( P = .017), NEFH ( P = .023) regarding DSS, and PCDH17 ( P = .001) regarding DFS. Our study not only highlights the prognostic value of promoter methylation of PCDH17 and NEFH in cancer tissues but also is the first report of the prognostic value of methylation alterations in normal tissues. Our findings are the first report of the prognostic value of methylation alterations in normal tissues, which can contribute to improved assessment of recurrence risk.